2015
DOI: 10.3390/molecules201119693
|View full text |Cite
|
Sign up to set email alerts
|

Derinat Protects Skin against Ultraviolet-B (UVB)-Induced Cellular Damage

Abstract: Ultraviolet-B (UVB) is one of the most cytotoxic and mutagenic stresses that contribute to skin damage and aging through increasing intracellular Ca 2+ and reactive oxygen species (ROS). Derinat (sodium deoxyribonucleate) has been utilized as an immunomodulator for the treatment of ROS-associated diseases in clinics. However, the molecular mechanism by which Derinat protects skin cells from UVB-induced damage is poorly understood. Here, we show that Derinat significantly attenuated UVB-induced intracellular RO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 40 publications
2
22
0
Order By: Relevance
“…Our discovery that TRPC7 is a nociceptive mechanoreceptor, together with our previous finding that TRPC7 has a role in UVB‐induced skin aging via increased ROS production (Hsu et al, ), is consistent with the previously reported links between nociceptive TRP receptors and aging (Buffenstein, ; Park et al, ; Riera et al, ; Seluanov et al, ). Interestingly, TRP channel expression has been previously shown to increase with age‐related degeneration (Santoni & Farfariello, ; Takada et al, ; Yue et al, ), but our results suggest that TRP channels, especially nociceptive TRP channels, are also important in initiating the aging process.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our discovery that TRPC7 is a nociceptive mechanoreceptor, together with our previous finding that TRPC7 has a role in UVB‐induced skin aging via increased ROS production (Hsu et al, ), is consistent with the previously reported links between nociceptive TRP receptors and aging (Buffenstein, ; Park et al, ; Riera et al, ; Seluanov et al, ). Interestingly, TRP channel expression has been previously shown to increase with age‐related degeneration (Santoni & Farfariello, ; Takada et al, ; Yue et al, ), but our results suggest that TRP channels, especially nociceptive TRP channels, are also important in initiating the aging process.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the knockdown of TRPC7 inhibited UVB‐induced p53 expression in keratinocytes (Figure e–g), which was corroborated by our observation that the UVB‐induced activation of the p53 pathway was reduced in TRPC7 +/− and TRPC7 −/− mice (Figure i). In addition, extracellular Ca 2+ influx is known to induce cyclooxygenase‐2 (COX‐2) expression, which increases p53 pathway activation and promotes the aging process (Hsu et al, ; Kim et al, ). We found that after UVB exposure, the high levels of COX‐2 protein expression observed in the epidermis of wild‐type mice were decreased to minimal levels in TRPC7 +/− and TRPC7 −/− mice (Figure h).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thymomimetic agents turned out to be lipid metabolism regulators, reduced blood glucose levels, and normalized liver function indicators. In patients with chronic pyelonephritis, galavit resulted in the normalization of creatinine and bilirubin; super lymph -creatinine; derinat -urea, creatinine, ALAT and ASAT (Hsu et al 2015). Nucleic acid preparations -sodium nucleinate, ridostin, derinat, poludan, isoprinosine -manifested not only differentiated immunocorrective, but also metabolic effects (Daniels et al 2018).…”
Section: Metabolic Effects Of Immunomodulatorsmentioning
confidence: 99%